Energy Efficiency in the Building Sector in Burkina Faso: Literature Review, SWOT Analysis, and Recommendations - Bazam Amonet Ouoba Nebie; Abdou Lawane; Césaire Hema; Monica Siroux (Energies)
In Burkina Faso, increasing access to electricity requires the optimized management of energy consumption in buildings and the implementation of regional and national regulations. These regulations have been implemented to promote energy efficiency in the building sector. However, they do not yet seem to have produced the expected results. Conducting a study could help identify the shortcomings related to energy efficiency and guide future research toward sustainable solutions. To date, no such study has been carried out. Therefore, this research aims to analyze the causes of these shortcomings, understand the gaps in the literature, and identify prospects for implementing energy efficiency policy in buildings in Burkina Faso. The methodology consisted of systematically analyzing the scientific literature on current regulations and previous scientific studies on energy efficiency in Burkina Faso. A SWOT analysis of energy efficiency programs in buildings in Burkina Faso was then carried out, and recommendations were proposed. The results show that the obstacles to the emergence of a genuine energy efficiency program in buildings are the inadequacies of the texts and regulations in force, the lack of standards, and the focus of scientific studies on building materials to the detriment of residents’ consumption habits. This study, therefore, sets out guidelines for future research and policies, while providing recommendations for improving the energy efficiency of buildings in Burkina Faso.